Rituximab Prevents the Development of Experimental Autoimmune Encephalomyelitis (EAE): Comparison with Prophylactic, Therapeutic or Combinational Regimens - Al-ani MR; Raju TK; Hachim MY; Hachim IY; Elemam NM; Guimei M; Bendardaf R; Maghazachi AA (Dove Medical Press, 2020)
Mena R Al-ani,1 Tom K Raju,2 Mahmood Y Hachim,1,2 Ibrahim Y Hachim,1 Noha M Elemam,1,2 Maha Guimei,1,3 Riyad Bendardaf,4 Azzam A Maghazachi1,2 1Department of Clinical Sciences, College of Medicine, University of Sharjah, Sharjah, 27272, United Arabs Emirates; 2Sharjah Institute for Medical Research (SIMR), University of Sharjah, Sharjah 27272, United Arabs Emirates; 3Alexandria University, Alexandria, Egypt; 4University Hospital Sharjah, Sharjah, United Arabs EmiratesCorrespondence: Azzam A MaghazachiDepartment of Clinical Sciences, College of Medicine, University of Sharjah, University City Road, Sharjah 27272, United Arabs EmiratesTel +971 554999175Email amagazachi@sharjah.ac.aeObjective: To investigate, in detail, the effects of rituximab (RTX), an off-label drug for treating multiple sclerosis (MS) disease on preventing and/or ameliorating experimental autoimmune encephalomyelitis (EAE).Methods: Using bioinformatics analysis of publicly available transcriptomics data, we determined the accumulation of B cells, plasma cells and T cells in different compartments of multiple sclerosis patients (MS) and healthy individual brains. Based on these observations and on the literature search, we dosed RTX in EAE mice either orally, or injected intraperitoneally (IP). The latter route was used either prophylactically (asymptomatic stage; upon the induction of the disease), or therapeutically (acute stage; upon the appearance of the first sign of the disease). Further, we used RTX as a preventive drug either as a single agent or in combination with other routes of administration.Results: Because no complete recovery was observed when RTX was used prophylactically or therapeutically, we devised another protocol of injecting this drug before the onset of the disease and designated this regiment as prevention. We demonstrated that the 20 μg/mouse prevention completely reduced the EAE clinical score, impaired infiltration of T and B cells into the perivascular space of mice brains, along with inhibiting the inflammation and demyelination. However, the 5 and 10 μg/mouse doses although reduced all aspects of inflammation in these mice, their effects were not as potent as the 20 μg/mouse RTX dose. Finally, we combined the 5 μg/mouse prevention treatment with either the prophylactic or therapeutic regimen and observed a robust effect.Conclusion: We observed that combinatorial regimens resulted in further reduction of inflammation, T and B cell extravasation into the brains of EAE mice and improved the re-myelination.Keywords: rituximab, inflammation, prevention, prophylactic, therapeutic, T cells, B cells, in silico, bioinformatics, immunohistochemistry